Novel PI3kδ inhibitor roginolisib synergizes with venetoclax in hematologic malignancies - Binu Kandathilparambil Sasi; Chiara Tarantelli; Stephen Martindale; Elisa Civanelli; Eleonora Cannas; Giulio Sartori; Alberto J. Arribas; Stacey M. Fernandes; Samantha J. Shupe; John-Hanson Machado; Svitlana Tyekucheva; Yue Ren; et al. (Haematologica)
The phosphoinositide 3-kinase (PI3K) pathway remains a potent drug target in hematological malignancies despite the challenges that have affected clinical drug development, particularly unpredictable toxicity, and inherent/acquired drug resistance. Herein, we tested the activity of a novel PI3Kδ selective, non-ATP competitive inhibitor, roginolisib (IOA-244), in hematological malignancies including diffuse large B cell lymphoma (DLBCL) and chronic lymphocytic leukemia (CLL). To identify rational actionable combination partners that can be tested in hematologic malignancies, an unbiased pharmacological screening of 474 compounds was carried out in two lymphoma cell lines. We identified BCL2 blockade with venetoclax as synergistically active with roginolisib, a finding confirmed in a broad panel of lymphoma cell lines, DLBCL cell lines and primary CLL samples. We further demonstrate that the sensitizing effects of roginolisib to venetoclax correlate with suppression of downstream PI3K/AKT pathways and alterations in the expression of the apoptotic proteins BIM, mediated through FOXO1 transactivation, and MCL1, with ubiquitination and degradation mediated through GSK3α/β activation. These findings support proof of concept for roginolisib development in hematological malignancies as a single agent or in combination with venetoclax. A clinical trial of roginolisib with venetoclax and an anti-CD20 antibody is initiating in CLL.